The impact of playing a snakes and ladders game about Mount Merapi disaster awareness on students' preparedness knowledge at Kepuharjo Cangkringan Elementary School - nugroho, ariyanto; Rahmuniati, Merita Eka; Sahayati, Sri; Polnesta Ita, Maria Denliana (Universitas Negeri Semarang, 2025)
Background: Indonesia is a country that is highly susceptible to natural disasters, particularly due to the frequent volcanic eruptions occurring on the island of Java. This situation underscores the importance of ensuring that students in disaster-prone regions are well-prepared for such events. Traditional outreach methods have often been deemed insufficient in enhancing students' understanding of disaster preparedness. In response to this challenge, this research introduces an innovative educational tool: modified